50.9k views
5 votes
Helpppppp , quick answer with work pleaseeee​

Helpppppp , quick answer with work pleaseeee​-example-1
User Ben Harold
by
5.2k points

1 Answer

3 votes

Answer:

Explanation:


√(x-2)+8=x\\\\√(x-2)=x-8\\

Square both sides,


x-2=(x-8)^(2)\\\\x-2=x^(2)-2*x*8+8^(2)\\\\x-2=x^(2)-16x+64\\\\x^(2)-16x+64=x-2\\\\x^(2)-16x+64-x+2=0\\\\x^(2)-17x+66=0

Sum = - 17

Product = 66

Factors = -6 , -11

x² - 6x -11x + (-6)*(-11) = 0

x(x - 6) -11(x - 6) = 0

(x-6) (x - 11) = 0

x -6 = 0 ; x - 11 = 0

x = 6 ; x =11

Here, x = 6 is a extraneous solution

User Cay
by
4.3k points